Basic principles of sports nutrition - Grout, A.; McClave, S. A.; Jampolis, M. B.; Krueger, K.; Hurt, R. T.; Landes, S.; Kiraly, L. (Current Nutrition Reports, 2016)
Proper nutrition is a key component in the preparation and training of the competitive athlete. The dietary recommendations for sports nutrition are surprisingly conventional, similar to that for the prevention of chronic disease (such as cancer, diabetes, stroke, hypertension, and cardiovascular disease). Few specialized supplements are required above a well-balanced diet of sufficient protein and carbohydrate. Total caloric requirements, macronutrient composition, and need for electrolyte/micronutrient repletion may vary from one sport to another (and between various positions within a single sport). The type and duration of the sporting event affect the utilization of energy systems, substrate availability, and the training adaptations required to optimize athleticism. Undernutrition, dehydration, and electrolyte abnormalities can reduce cognition, endurance, thermoregulation, overall performance, and recovery. A properly designed dietary program throughout training, competition, and the off-season should benefit and help protect both the recreational and the elite athlete.